Analisis perbandingan rencana strategis pada perbankan swasta di Indonesia - Sabita, Azmi; Fadlilah, Lailatul Iftitachatil; Affandy, Faza Ainunnisa (Maliki Interdisciplinary Journal, 2023)
Banks are industries or companies that operate in the field of public financial services through activities of collecting funds in the form of savings and channeling them back to the community in the form of credit. In every development of banking institutions, efforts are needed that can improve banking operational activities. One effort that can be carried out by banks is strategic planning. The purpose of this research is to find out the comparison of strategic plans at Bank Danamon, Maybank Indonesia and Bank Permata. The purpose of comparing the strategic plans of each bank is of course to have a strategic plan that is in accordance with their respective visions, which can then lead the bank to the goals and target areas it wants to achieve. Of course, Bank Danamon, Maybank, Bank Permata have different strategic plans. Banking institutions have experienced very rapid development. One of the factors for successful development in banking institutions is a good and appropriate strategic plan. Bank Danamon, Maybank, and Bank Permata have made strategic plans that can make their companies develop further. With different development focuses, the three banks also have their respective advantages and disadvantages.